The Role of Distribution Channels and Educational level towards Insurance Awareness among the General Public - Waseem-Ul- Hameed; Muhammad Azeem; Mohsin Ali; Shahid Nadeem; Tayyab Amjad (International Journal of Supply Chain Management, 2017)
This research study aims at giving an overview of the emerging research field of Islamic insurance in a phase that is still under debate among Muslim nations. No doubt, Takaful (Islamic insurance) is growing rapidly but it is still behind conventional insurance. Most of the researches reveal the fact that general public is unaware about Takaful and Takaful awareness level is low among general public. Researchers and practitioners are trying to explore the crucial factors which creates Takaful awareness among general public. However, only few studies are available in Pakistan which formally documented the issue and explore different Takaful awareness factors among general public of Pakistan. Therefore, the ultimate objective of this study is to find out general factors which enhance Takaful awareness level among general public of Pakistan. To achieve this objective, three hypotheses are proposed concerning the relationship of Takaful awareness level and other Takaful awareness factors such as Educational Level of general public, Religious Orientation of general public and Takaful Distribution Channels. Primary data was collected from general public of Pakistan by using 5-point Likert scale. These hypotheses predicting a positive relationship between Takaful awareness level and awareness factors (i.e., educational level, religious orientation, distribution channels). However, religious orientation has higher impact as compared to Takaful distribution channels and educational level. Study found that these three factors are crucial to enhance Takaful awareness level among general public. Hence, this study is contributing in the body of knowledge by exploring the vital factors to enhance Takaful awareness level and tried to resolve the important issue of Takaful awareness by developing a framework. This study is more significant for practitioners to enhance Takaful awareness level by exercising these three factors among general public of Pakistan.